Implementasi Program G3 Ctps (Gerakan Gosok Gigi Dan Cuci Tangan Pakai Sabun) Untuk Meningkatkan Perilaku Hidup Bersih Dan Sehat Di Sekolah Dasar (Sd) Desa Sojomerto - Nabela Devinta Puspitaningrum; Shevylia Cahya Ayu Saputri; Afra Mufida; Siska Eliana; Laila Haniatun Nasikah; Nahnu Robid Jiwandono (Lembaga Pengembangan Kinerja Dosen, 2024)
Dental health problems and a lack of handwashing with soap remain issues among elementary school students in Desa Sojomerto. This study implemented a Toothbrushing and Handwashing with Soap Movement program to address these problems. Through a series of educational activities and hands-on practice, the program aimed to change students' behaviors towards cleanliness and health. The research results showed a significant increase in toothbrushing frequency, correct handwashing techniques, and students' knowledge of the importance of hygiene.